Fixing the climate strategies for an uncertain world - Sabel, Charles (Princeton Princeton University Press, 2022)
Charles Sabel and David Victor explain why the profound transformations needed for deep cuts in emissions must arise locally, with government and business working together to experiment with new technologies, quickly learn the best solutions, and spread that information globally. Sabel and Victor show how some of the most iconic successes in environmental policy were products of this experimentalist approach to problem solving, such as the Montreal Protocol on the ozone layer, the rise of electric vehicles, and Europe?s success in controlling water pollution. They argue that the Paris Agreement is at best an umbrella under which local experimentation can push the technological frontier and help societies around the world learn how to deploy the technologies and policies needed to tackle this daunting global problem.
Keywords: Environmental policy--International cooperation